Cover her face - James, P. D. (Adam Dalgliesh mystery, 2020)
"Headstrong and beautiful, the young housemaid Sally Jupp is put rudely in her place, strangled in her bed behind a bolted door. Coolly brilliant policeman Adam Dalgliesh of Scotland Yard must find her killer among a houseful of suspects, most of whom had very good reason to wish her ill."--Amazon.com